Inhibitory effect of DMSO, Tween 80 and Triton X-100 on Agaricus bisporus and Lecanicillium fungicola - Lee, Lundoi Tobias (2023)
Surfactants are substances widely used in the preparation of suspensions of spores, especially of ascomycete fungi. Among these studies are those that evaluate the use of antifungal compounds. However, these compounds, in addition to being good dispersants, may also have a synergistic or additional inhibitory effect to the action of the tested antifungals on spore germination or mycelial growth. Therefore, it is vital to evaluate this type of effect before its use in this type of test. The fungus Lecanicillium fungicola is the causative agent of dry bubble disease, which affects the cultivation of the button mushrooms (Agaricus bisporus). In addition to preparing the spore suspension, surfactants are used in the solubilization or preparation of essential oil emulsions tested in the control of L. fungicola. The aim of this study was to evaluate the influence DMSO (solvent and a weak surfactant) and two surfactants: (Tween 80 and Triton X-100) at the concentrations of 0.5 and 1%, on the mycelial growth of L. fungicola and A. bisporus. For DMSO, no visual changes were observed in the colonies for both species. Tween 80 affected mycelial growth, causing colonies to grow less when compared to control, in addition to changing the morphology of the colony for both species. Triton X-100 showed an even greater inhibitory effect on the growth of the two fungal species, considerably affecting both the size and the morphology of the colony. Scanning electron microscopy analysis showed that surfactants alter the structures and aspects of the hyphae of both fungi and in the case of L. fungicola they also affected the quantity and aspect of the spores.